WhatsApp in emergency remote learning: The students’ perception - Wulandari, Eka; Mandasari, Yuyun Putri (Universitas Muhammadiyah Sidoarjo, 2021)
The emergency remote learning due to COVID-19 pandemic and the government strategy to move the lesson into online mode make language learning technologies play an important role to help students achieving the goals of learning. WhatsApp application as one of learning media offers some benefits that can be utilized by the students and teachers to achieve this goal. This study aimed at knowing the midwifery and nursing students‘ perception on the use of WhatsApp as the media of English teaching and learning process in the context of Emergency Remote Learning (ERL). This paper presented data survey towards 183 students of nursing and midwifery departments at Poltekkes Kemenkes Malang. The instrument of this study was an online questionnaire designed based on the literature review and administered to the participants through class‘s WhatsApp Group. There were 25 items in the questionnaire and the content was conveyed the demographic data and students’ perception towards the use of WhatsApp application that helped them mastering four English language skills and components as well as getting scoring and feedback. The data were presented in the percentage data and analyzed using descriptive explanation. The finding showed that students’ perception on WhatsApp as learning media in English online learning in ERL context gained highly positive perception on all items. Based on this result, teachers can utilize all features on WhatsApp to design meaningful learning in the time of emergency remote teaching and learning. HIGHLIGHTS : Students’ perception on WhatsApp as learning media in English online learning in ERL context gained highly positive perception on all items There are some drawbacks regarding the use of WhatsApp application for online setting during ERL, so some strategies should be implemented to minimize them Teachers can utilize all features on WhatsApp to design meaningful learning during thisemergency remote teaching and learning period